Effects of treatment on Lantana camara (L.) and the restoration potential of riparian seed banks in cleared areas of the Victoria Falls World Heritage Site, Livingstone, Zambia - Nang'alelwa, Michael Mubitelela (Rhodes University, Faculty of Science, Botany Department, 2010)
The exotic plant Lantana camara L. has invaded the riparian areas of the Victoria Falls World Heritage Site in Livingstone, southern Zambia, threatening native plant communities which support populations of species of special concern. I trialled the mechanical control method of manual uprooting and 3 different herbicides applied through paint brushing of an imazapyr concentrate at 250g. l¯¹, spraying on cut stumps with metsulfron methyl at 600g.l¯¹, and foliar spraying on re-emergent lantana foliage with glyphosate at a dosage of 166g. l¯¹ in July 2008 in 20 100m2 treatment plots, 5 invaded control plots and 5 uninvaded controls. Follow-up treatments for re-sprouting lantana stumps and emerging seedlings were undertaken in June 2009. I measured effectiveness of the methods using adult lantana mortality in June 2009 and lantana seedling density in the different treatment plots during the follow-up exercise. The cost of the various methods and human labour applied were compared across the four treatments at initial clear and at follow-up. All treatments recorded a high adult lantana mortality rate, though there were no significant differences in lantana adult mortality amongst the treatments. Overall, uprooting had the highest adult mortality, followed by imazapyr, metsulfron and lastly glyphosate. Germination of lantana seedlings after clearing was high for all treatments but with no significant differences occurring between the treatments. Both adult lantana mortality and seedling density were however significantly different from the control. With labour included, chemical costs were far higher relative to uprooting, though uprooting costs were the highest when it came to the follow-up because of the emerging seedlings and some resprouting stumps. The effects of mechanical and chemical treatments on vegetation composition in the cleared areas were also assessed in order to detect any non-target and medium term effects of treatments. Contrary to expectation, none of the chemicals showed any significant effects on vegetation composition in the short and medium-term and no significant differences were found in plant species richness, diversity and seedling density between invaded and uninvaded plots at baseline, in October 2008 and in September 2009. In order to determine potential for unaided vegetation recovery in the riparian areas of the study site after lantana clearing, I conducted an investigation of soil seed banks and seed rain using 60 seed bank samples measuring 1800m³ collected from 30 invaded and uninvaded plots. Using the seedling emergence method, 1, 991 seedlings belonging to 66 species representing 27 families germinated from the seed bank. Sedges (Cyperaceae family) were the most abundant taxa in the seed banks from invaded areas, followed by Ageratum conyzoides, lantana, Triumfetta annua and Achyranthes aspera which also occurred in the uninvaded soil seed banks. The seed banks from uninvaded plots were dominated by the grass Oplismenus hirtellus. Overall, species richness, diversity and seedling density from seed banks in invaded areas did not differ significantly from seed bank in uninvaded areas and there was a low similarity in species composition when above ground vegetation was compared to seed banks from invaded and uninvaded areas. It would appear if natural regeneration occured from the current seed bank in disturbed areas, future vegetation would largely comprise of short lived, early successional species in the short term as the seed bank is dominated by non-native herbaceous weedy species. From the seed traps investigating seed rain, a total of 27 species numbering 623 individual seeds were found in the thirty 1m² seedtraps distributed in invaded and uninvaded areas at the five sites, over an intermittent period of three months. Lantana had the highest monthly arrival rate in the seed traps followed by Phoenix reclinata and Ricinus communis. The number of species with invasive potential found in the seed traps located in invaded areas was more than that found in seed traps under native vegetation cover by far. Considerable forest remnants still occur around the invaded sites, and these could serve as an important source for long-term natural re-establishment of native vegetation if seed availability by animals and wind dispersal continues, while the re-invasion of lantana is prevented by ongoing follow-ups and futher clearing of lantana invaded areas. It is concluded that while uprooting and other treatments are effective in the control of lantana, its successful control in the Victoria Falls World Heritage Site will require extensive clearing to keep it from reinvading infested areas after clearing as shown by the seed rain data. The high seedling density of lantana in the seed banks and in the cleared areas shows the need for ongoing follow-up in order to deplete soil stored seed banks. There is need for longer term research to establish what the exact follow-up requirements are in order to contain lantana re-infestation and create favourable micro-sites for native species to establish. It is predicted that ongoing lantana control in the cleared plots will most likely initiate long-term community recovery.
Keywords: Lantana camara -- Victoria Falls (Zambia and Zimbabwe); Lantana camara -- Biological control -- Victoria Falls (Zambia and Zimbabwe); Invasive plants -- Biological control -- Victoria Falls (Zambia and Zimbabwe); Riparian restoration -- Victoria Falls (Zambia and Zimbabwe); Riparian ecology -- Victoria Falls (Zambia and Zimbabwe)